Do the business cycle and revenue diversification matter for banks' capital buffer and credit risk: Evidence from ASEAN banks. Issue 1 (April 2020) - Ovi, Nafisa; Bose, Sudipta; Gunasekarage, Abeyratna; Shams, Syed
Abstract: We examine the association of the business cycle and revenue diversification with the banks' capital buffer and credit risk for a sample of banks from the Association of Southeast Asian Nations (ASEAN) region from 1998 to 2018, using 2847 banking firm–year observations. We find that ASEAN region banks react anticyclically in adjusting their capital buffer levels and credit risk. We find revenue diversification benefits and that banks, through revenue diversification, can reduce their credit risk while achieving capital savings when confronting economic downturns. Our results offer support for the Basel III accord. However, the relations revealed are somewhat moderated by the regulatory quality, competition, and phase of the business cycle encountered by ASEAN region banks.